Assembly of Hybrid Materials Based on a Lanthanide–Organic Framework and a Keggin‐Type [PMo12–xVxO40](3+x)– (x = 1, 2) Cluster. Issue 12 (6th February 2013) - Liu, Xiaoyu; Wang, Li; Yin, Xuena; Huang, Rudan
Abstract: A series of hybrid compounds based on polyoxometalates (POM), namely, [Ln4 (pdc)4 (H2 O)16 ][PMo11 VO40 ]· 2H2 O (1 –5 ) and [Ln4 (pdc)4 (H2 O)16 ][HPMo10 V2 O40 ]· H2 O (6, 7 ) (Ln = La, Ce, Pr, Nd, Sm for1 –5, respectively, and Ln = La and Ce for6 and7, respectively; H2 pdc = pyridine‐2, 6‐dicarboxylic acid), were hydrothermally synthesized and characterized by IR spectroscopy, elemental analyses, XRD, and single‐crystal X‐ray diffraction analyses. In these compounds, the Keggin polyanions [PMo12– x V x O40 ] (3+ x )– ( x = 1, 2) are encapsulated as noncoordinating guests in the nonlinear channels of the 3D lanthanide–pdc‐based host framework with a 4 3 · 6 2 · 8 topology. Moreover, photoluminescent properties, electrochemical properties, and catalytic properties were investigated. Abstract : A series of polyoxometalate‐based hybrid compounds, [Ln4 (pdc)4 (H2 O)16 ][PMo11 VO40 ]· 2H2 O (1 –5 ) and [Ln4 (pdc)4 (H2 O)16 ][HPMo10 V2 O40 ]· H2 O (6, 7 ) (Ln = La, Ce, Pr, Nd, Sm for1 –5 and Ln = La and Ce for6 and7 ; H2 pdc = pyridine‐2, 6‐dicarboxylic acid), were synthesized and characterized. Moreover, photoluminescent properties, electrochemical properties, and catalytic properties were investigated.